2003
DOI: 10.1029/2002gb001964
|View full text |Cite
|
Sign up to set email alerts
|

Flux and bioavailability of Cape Fear River and rainwater dissolved organic carbon to Long Bay, southeastern United States

Abstract: [1] This study presents the first comparison of riverine and rainwater dissolved organic carbon (DOC) flux to a coastal region, and the first examination of rainwater DOC bioavailability. The bioavailability of DOC from these two sources was determined because its impact on coastal waters depends on whether DOC is labile or refractory. The study site, Long Bay, off the North Carolina and South Carolina coasts in the southeastern United States, receives external sources of DOC from the Cape Fear River system an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
38
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(43 citation statements)
references
References 34 publications
4
38
1
Order By: Relevance
“…Vol. 65, 2003 Research Article 395 A recent study has also shown that DOC is conservatively mixed in the Cape Fear Estuary (Avery et al, 2003). Because CDOM absorption is negatively correlated with salinity, we expected similar results relating the percent contribution of respective peak intensities to the total EEM intensity and salinity, because fluorescence can be regarded as a proxy for CDOM absorption.…”
supporting
confidence: 70%
“…Vol. 65, 2003 Research Article 395 A recent study has also shown that DOC is conservatively mixed in the Cape Fear Estuary (Avery et al, 2003). Because CDOM absorption is negatively correlated with salinity, we expected similar results relating the percent contribution of respective peak intensities to the total EEM intensity and salinity, because fluorescence can be regarded as a proxy for CDOM absorption.…”
supporting
confidence: 70%
“…13 Possibility of alterations in the quality and quantity of root exudates has been raised in connection with studies that have reported UV-B-induced changes in soil microbial communities. 10,11,14 However, except rice and mire there are not enough studies on the effects of UV-B radiation on the fate of root exudate profile and associated rhizospheric changes in other plants. 11,15 UV-B radiation induces various adaptive morphological changes in plants such as leaf thickening and shortening, shifts in root: shoot ratio and alterations in reproductive structures.…”
Section: Discussionmentioning
confidence: 99%
“…12 Additionally, upon exposure to UV light, leachates from Phragmites leaves inhibited microbial growth as compared to an untreated control. 13 Although the possibility of alterations in the quality and quantity of root exudates has been raised in connection with studies that reported UV-B-induced changes in soil microbial communities, 10,11,14 we have no knowledge of controlled testing of the effects of increased UV-B radiation on root exudation or rhizospheric processes in any other plant system other than rice. 15 Most of the studies pertaining to the effect of UV light on plant growth ranges from wild plant species are limited to African savanna, 16 arctic ecosystems, 17 salt marshes 18,19 and Mediterranean ecosystems.…”
Section: Introductionmentioning
confidence: 99%
“…DOC was determined by high temperature combustion (HTC) using a Shimadzu TOC-5050A total organic carbon analyzer equipped with an ASI 5000 autosampler (Shimadzu, Kyoto, Japan) (Avery et al 2003). Standards were prepared using reagent grade potassium hydrogen phthalate (KHP) in deionized water (DIW).…”
Section: Doc Analysismentioning
confidence: 99%